(untitled) (Asian Journal of Medical and Biological Research, 2020)
Foreign body (FB) ingestion is common in children worldwide. Type of FB ingestion varies among cultures and countries. We retrospectively reviewed all patients of foreign body ingestion who were admitted in Department of Pediatric Surgery, Chittagong Medical College Hospital from January 2017 to December 2019 (total 3 years). Age, Sex, type of foreign body, hospital stay, management and outcome were analyzed. A total of 91 children were admitted with ingestion of FB during this period; male 61, female 30 (male to female ratio 2:1). Age ranged from 3 months to 12 years (median 3.5 ± 3.8 years). Fifty eight percent were less than 5 years old. Children ingested 21 different types of FB; however ingestion of coin was most common (24 patients, 26.37%) followed by different types of pins (19 patients, 20.88%), nail (6 patients, 6.59%), battery (5 patients, 5.49%), screw (5 patients, 5.49%), needle (4 patients, 4.40%), ring (4 patients, 4.40%) and others (18 patients). Sharp object ingestion is higher in older (>5 year) age group. Hospital stay ranged from 0 day to 19 days (mean 1.6 ± 2.1 day). Endoscopic removal needed in 4 patients (coin-2, chain 2), bronchoscopic removal in 1 (pin) and one patient needed laparotomy (open hair pin). There was no mortality. The pattern of FB ingestion is similar to many other countries. Small, smooth objects pass spontaneously. Endoscopic or surgical intervention is sometimes needed if significant symptoms develop or if the object fails to progress through the gastrointestinal tract. Asian J. Med. Biol. Res. June 2020, 6(2): 299-304